An investigation of soft magnetic and non magnetic materials under low frequency - Arshad, Atika; Khan, Sheroz; Alam, A. H. M. Zahirul; Tasnim, Rumana (IIUM Press, 2011)
The recent development of magnetic sensors in biomedical sector has called for urgent investigation on the characterization and relative magnetism of magnetic and nonmagnetic materials. This paper proposes a novel technique to categorize the magnetic and non-magnetic materials by obtaining their impedance peaks. The magnetization effect of a magneto-inductive sensor was detected in low frequency range for different magnetic and nonmagnetic core materials. The distinctive impedance peak values have been obtained for each materials used as core which result in showing different magneto-inductive effect. The results have shown a dominant behaviour of magnetic materials over non-magnetic materials due to the variation of permeability and magnetic strength (number of turns). Moreover, variations in permeability originated by the applied alternative current field results in changing the depth (insertion depth) and also in the impedance. The influence of the permeability on materials with different frequencies is detailed. Also, concentration is paid to the recent studies in the application base. It should be mentioned that high impedance peaks mean high output voltage in the secondary side. The novelty of this technique lies in the simplicity of ordinary circuits which are used in the experimental setup for haracterization purpose. As a whole, this paper aims to investigate and characterize magnetic and non-magnetic materials; thus opening up a new branch of research for the application of soft magnetic materials in biomedical field.